Cardiovascular Diseases and Drug Treatment in Patients with the History of Cerebral Stroke: Data of the Outpatient Registry REGION - M. M. Loukianov; S. S. Yakushin; S. Yu. Martsevich; O. M. Drapkina; A. N. Vorobyev; A. V. Zagrebelnyy; A. N. Kozminsky; K. A. Moseichuk; K. G. Pereverzeva; E. A. Pravkina; E. Yu. Okshina; E. V. Kudryashov; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the structure of combined cardiovascular diseases, drug treatment and observation of patients with a history of stroke in the framework of prospective outpatient registries. Material and methods. The study was conducted based on 3 outpatient clinics of Ryazan city. Patients with a history of acute cerebrovascular accident (ACVA) of any remoteness (AR) were included into ACVA-AR outpatient registry (n=511). Patients who had visited the outpatient clinics for the first time (FT) after cerebral stroke (n=475) were included into the ACVA-FT outpatient registry. The structure of the cardiovascular diseases (CVD), compliance with the clinical recommendations of the prescribed and received drug therapy were evaluated. The proportion of patients with dispensary observation for CVD, using preferential drug provision was determined. Results. A combination of 2 or more CVDs was found in 84.4% and 82.5% of cases, and severe cardiovascular multimorbidity (3-4 CVDs) – in 69% and 64% of cases, respectively, in ACVA-AR and ACVA-FT registers. Compliance with the clinical guidelines prescribed and received drug therapy was insufficient at the outpatient stage. Necessary prescription of drugs with a proven beneficial effect on the prognosis were observed significantly more frequent in the ACVA-FT registry, compared to the ACVA-AR registry at the enrolling stage of the study (p<0.05): statins for stroke – 50.1% vs 25.2%; statins for coronary heart disease (CHD) – 47.2% vs 27.9%; antiplatelet agents for CHD without atrial fibrillation – 65.6% vs 54.3%; anticoagulants for atrial fibrillation – 17.7% vs 9.3%; beta-blockers for heart failure 43.5% vs 33.1%, respectively. After 2-3 years of the follow-up frequency of prognostically significant prescriptions in patients of the compared registries were not significantly different, except prescriptions for statin therapy (47.6% vs 21.3%, respectively). The prognostically significant prescriptions during the enrolling stage in ACVA-AR and ACVA-FT registries occurred in 44.4% and 54% of the total number of proper prescriptions, and in the long-term follow-up period – in 55% and 57%, respectively; and the dispensary observation coverage was only 35.0% and 31.8%, respectively. According to patient contact only 21-24% of patients used the system of preferential drug provision at the stage of inclusion into the registers, and after 2-3 years of follow-up – 1.5-2 times less (12-14%). Conclusion The results of the study REGION found the presence of cardiovascular multimorbidity in 83% of patients with a history of stroke, insufficient quality of prescribed drug therapy in the out-patient clinic, especially in the ACVA-AR registry. The quality of medical treatment of patients improved within 2-3-year follow-up after the reference visit to out-patient clinic, but not sufficiently. Increase in dispensary observation coverage and optimization of the system of preferential drug provision are also important reserves for improving the quality of treatment of patients with a history of stroke, as well as prevention of cardiovascular complications.